PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BERTUKAR PASANGAN TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 9 PADANG TAHUN PELAJARAN 2013/2014 - Harmizawati, Iing; Nasution, Minora Longgom; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
This research based on the mathematic conceptual understanding of students is low and the students do not want to give and share their knowledge eatch other, itâs mean they are individualis in teaching learning proses. This the goal of research is to know now studentâs mathematics concept by using cooperative learning model type of changing partner is better than understanding of mathematic concept by using kobventional learning in class XI IPA SMAN 9 Padang in academic year 2013/2014. Kind of this research is experimental research, by random sampling. The population of the research is the second year students of SMAN 9 Padang in academic year 2013/2014 that included in 6 classes. The samples is XI IPA 1 as eksperiment class and class XI IPA 2 as control class. The instrument is an essay test with reliabilitas test is r11 = 0,61. Teachnigue of data analisys is Mann-Whitney teste. The hypotesist tested by used Mann-Whitney test. For validity grade 95% is and, becauseÂ andÂ inÂ area is rejected, soÂ is rejected and Â is accepted. Itâs mean the studentâs understanding of mathematic concept by using cooperative learning model type of changing partner is better than the understanding of studentâs mathematic concept by using conventional learning in class XI IPA SMAN 9 Padang in academic year 2013/2014.